WHAT SHOULD BE DONE WHEN LISTENING COMPREHENSION IS DIFFICULT? - Hariswan Putera Jaya (Politeknik Negeri Sriwijaya, 2017)
Listening comprehension is a course which students majoring in English must take. It is also a part of every English competence test. It is usually considered as a difficult course just because students usually have problems in understanding what they are listening either in classrooms or in tests. There are factors which contribute to these problems. Students and teachers must recoqnize these problems in order to have better listening comprehensions. There are also suggestions to solve these problems. This paper is discusing why listening comprehension is difficult and possible solutions which students and teahers can do.